2001
DOI: 10.1007/bf02492254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the solvent on the gas chromatographic behaviour of urea herbicides

Abstract: SummaryDegradation products of chlorsulfuron, chlortoluron, diuron, fluometuron, isoproturon, Iinuron, metabenzthiazuron, metobromuron, and monuron formed in the gas chromatographic injector have been used for identification of the respective herbicides. Mass spectra of the derived compounds were obtained with a quadrupole mass spectrometric detector working in scan mode (20-450 amu). The compounds generated often depended on the solvent used for phenylurea herbicide injection (ethanol, methanol, dichlorometha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Under controlled conditions phenylureas can be determined from waters by SPME-GC in form of their respective derived anilines [32]. The gas chromatographic behaviour of the urea herbicides has been recently studied [33][34][35], the use of high temperatures at the injector port facilitates the degradation of the herbicide in a derived product, which depends on the solvent used for injection [36].…”
Section: Introductionmentioning
confidence: 99%
“…Under controlled conditions phenylureas can be determined from waters by SPME-GC in form of their respective derived anilines [32]. The gas chromatographic behaviour of the urea herbicides has been recently studied [33][34][35], the use of high temperatures at the injector port facilitates the degradation of the herbicide in a derived product, which depends on the solvent used for injection [36].…”
Section: Introductionmentioning
confidence: 99%
“…The analogous carbamic acid methyl esters were found instead of the phenylurea herbicides. 2-aminobenzothiazol was found from metabenzthiazuron and 2-amino-4-methoxy-6-methyl-l,3,5-triazine from chlorsulfuron [36].…”
Section: Resultsmentioning
confidence: 99%
“…Other authors [21,27,29,30] reported phenylurea determination in form of their analogous phenylisocyanates but they used different non-alcoholic solvents for injection. The importance of the solvent in the GC analysis of urea herbicides has been recently studied [36]. Figure 1 shows the chromatograms obtained from the three GC instruments using different injection modes.…”
Section: Resultsmentioning
confidence: 99%
“…26 Capillary electrophoresis [27][28][29] and multivariate calibration methods 30 have been also employed.…”
Section: Introductionmentioning
confidence: 99%